Identification of Differential Roles of MicroRNA‐33a and ‐33b During Atherosclerosis Progression With Genetically Modified Mice. Issue 13 (2nd July 2019) - Koyama, Satoshi; Horie, Takahiro; Nishino, Tomohiro; Baba, Osamu; Sowa, Naoya; Miyasaka, Yui; Kuwabara, Yasuhide; Nakao, Tetsushi; Nishiga, Masataka; Nishi, Hitoo; Nakashima, Yasuhiro; Nakazeki, Fumiko; et al.
Abstract : Background: MicroRNA (miR)‐33 targets cholesterol transporter ATP‐binding cassette protein A1 and other antiatherogenic targets and contributes to atherogenic progression. Its inhibition or deletion is known to result in the amelioration of atherosclerosis in mice. However, mice lack the other member of the miR‐33 family, miR‐33b, which exists in humans and other large mammals. Thus, precise evaluation and comparison of the responsibilities of these 2 miRs during the progression of atherosclerosis has not been reported, although they are essential. Methods and Results: In this study, we performed a comprehensive analysis of the difference between the function of miR‐33a and miR‐33b using genetically modified mice. We generated 4 strains with or without miR‐33a and miR‐33b. Comparison between mice with only miR‐33a (wild‐type mice) and mice with only miR‐33b (miR‐33a −/− /miR‐33b +/+ ) revealed the dominant expression of miR‐33b in the liver. To evaluate the whole body atherogenic potency of miR‐33a and miR‐33b, we developed apolipoprotein E–deficient/miR‐33a +/+ /miR‐33b −/− mice and apolipoprotein E–deficient/miR‐33a −/− /miR‐33b +/+ mice. With a high‐fat and high‐cholesterol diet, the apolipoprotein E–deficient/miR‐33a −/− /miR‐33b +/+ mice developed increased atherosclerotic plaque versus apolipoprotein E–deficient/miR‐33a +/+ /miR‐33b −/− mice, in line with the predominant expression of miR‐33b in the liver and worsened serum cholesterol profile. By contrast, a bone marrow transplantation study showed no significant difference, which was consistent with the relevant expression levels of miR‐33a and miR‐33b in bone marrow cells. Conclusions: The miR‐33 family exhibits differences in distribution and regulation and particularly in the progression of atherosclerosis; miR‐33b would be more potent than miR‐33a.